1996
DOI: 10.1007/bf00218842
|View full text |Cite
|
Sign up to set email alerts
|

Apparent higher frequency of phenylketonuria in the Mexican state of Jalisco

Abstract: The geographic origin of Mexican patients with phenylketonuria (PKU) in Mexico City and in southern California was studied. Compared to patients with other metabolic disorders, patients with PKU were significantly more likely to have originated from the Los Altos region of the state of Jalisco and its environs. The incidence of PKU among mentally retarded students attending special education schools was found to be significantly higher in Jalisco (particularly the Los Altos region) than in the neighboring stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…The hypothesis that there is a higher PKU prevalence in this area was published several years ago, but has not been confirmed. 30 The clinical data described in Figure 2 are similar to the natural history of the disease reported in the literature, mostly affecting the central nervous system. 1 Contrary to what happens in developed countries, where PKU has grown from a symptomatic disease to a genetic condition modified by early treatment, 31 -33 we still treat patients with the whole phenotypic spectrum.…”
Section: Discussionsupporting
confidence: 70%
“…The hypothesis that there is a higher PKU prevalence in this area was published several years ago, but has not been confirmed. 30 The clinical data described in Figure 2 are similar to the natural history of the disease reported in the literature, mostly affecting the central nervous system. 1 Contrary to what happens in developed countries, where PKU has grown from a symptomatic disease to a genetic condition modified by early treatment, 31 -33 we still treat patients with the whole phenotypic spectrum.…”
Section: Discussionsupporting
confidence: 70%
“…This interpretation is consistent with the settlement history of Mexico, especially by individuals from southern Spain, who colonized El Bajío, particularly the state of Jalisco (‘Los Altos’ region) and its surroundings, during the XVI century . These results support a founder effect and/or genetic drift for c.60+5G>T but not for the Mediterranean c.1066‐11G>A, as was previously suggested .…”
Section: Discussionmentioning
confidence: 99%
“…The mutational spectrum of PAH in Mexico is poorly known; the only study that has been conducted, showed the presence of the c.1066‐11G>A in 5/14 alleles . There is some evidence that PKU in Mexico has a predominance of cases occurring in the Middle West of the country, mainly in the state of Jalisco, where a possible founder effect has been suggested . The PAH genotype, as a predictor of metabolic phenotype, has come to play an important role in assessing the potential responsiveness to treatment with sapropterin dihydrochloride, a synthetic formulation of the active naturally cofactor for PAH, tetrahydrobiopterin (BH 4 ) .…”
mentioning
confidence: 99%
“…Since most of our patients came from the central region of Mexico, the low allelic heterogeneity found might be explained by a Bpopulation of origin^effect-the introduction of few mutant alleles in a region by the immigration of a population which later spread. In the first two centuries of Spanish colonization, most immigrants to the central region of Mexico came from southern Spain (Marqué z-Morfín 1993) and probably introduced few galactosaemic alleles into this region of the country; this effect was described for phenylketonuria in Mexico (Velá zquez et al 1996), but further studies are required to confirm this hypothesis.…”
Section: Resultsmentioning
confidence: 76%